Habrophlebia hassainae, a new mayfly species (Ephemeroptera: Leptophlebiidae) from North Africa - Benhadji, Nadhira; Hassaine, Karima Abdellaoui; Sartori, Michel (Zootaxa, 2018)
We present here a new species of Habrophlebia, H. hassainae sp. nov., described at nymphal, imaginal and egg stages obtained by rearing from the Tafna watershed, North western Algeria. The new species was previously identified as H. cf. fusca by Gagneur & Thomas (1988). H. hassainae is in fact more related to H. lauta McLachlan, 1884, but can be separated by different characters on the male imago and nymphs. This is the third species of Habrophlebia reported from North Africa.